Sustaining Service Members and Their Families Exploring Opportunities for Efficiency and Joint Provision of Services Using Nonappropriated Funds - Connor, Kathryn (RAND Corporation, 2016)
The U.S. Department of Defense (DoD) sought to determine whether any administrative activities paid for with funding that was not congressionally appropriated could be consolidated-and, if so, whether consolidation would save costs. A DoD task force listed several areas for improvement, ranging from contracting to information technology. RAND reviewed the work of the task force and assessed specific recommendations.